Emerging from disruptions and ambiguities: Understanding local government innovative responses during the challenges of the COVID-19 pandemic. Issue 4 (December 2022) - Keyes, Laura; Jang, Hee Soun; Dicke, Lisa; Shi, Yu
This article investigates the utility of an integrated approach which combines the Incident Command System (ICS) model and the Disruption-Ambiguity-Innovation-Challenge model, for understanding local government homeless service responses during the COVID-19 pandemic. A case study in the City of Dallas, Texas is used to understand how three functional areas of the ICS (authority, operations, and finances), were influential in creating disruptions, ambiguities, innovations, and challenges for local government and its nonprofit partners. By using an integrated approach, we identify challenges, learning outcomes, and action strategies useful for consideration for local governments' strategies for crisis management.